(untitled) (American Journal of Business Management, Economics and Banking, 2024)
This study examines the influence of international financial organizations on the banking sector of Uzbekistan. By exploring the activities and impact of these organizations within Uzbekistan’s banking landscape, the research aims to shed light on the extent to which they shape financial policies, regulatory frameworks, and investment patterns. Through case studies and analysis, the work evaluates both the opportunities and challenges presented by such influence, offering insights into the dynamics of global financial partnerships and their implications for Uzbekistan’s economic development and financial stability.